DAMPAK KEBERADAAN JEMBATAN SURAMADU TERHADAP NILAI TANAH DI WILAYAH KAKI JEMBATAN SISI MADURA - Zuhriyah, Amanatuz; Ihsannudin, dan (Program Studi Agribisnis Fakultas Pertanian Universitas Trunojoyo Madura., 2013)
The construction of Suramadu Bridge give an impact on land values in foot bridge areas. This study aims to analyze the impact of the bridge on land values, before and after presence of the bridge. The results of this researchÂ shows land values at Labang is more thanÂ before. While, land values at Arosbaya, as control areas, has not changed significantly before and after the construction. The comparison between subject areas and control areas before the construction, were not significantly different. While, after the construction, there are significant differences between two samples tested, indicating that the existingÂ Suramadu bridge has impact to the land value at Labang compared to land values at Arosbaya, as control areas.